BIMBINGAN TEKNIS PEMBUATAN SABUN MANDI PADATAN UNTUK PKK RT.01/RW.01 POHJENTREK PASURUAN - Dwi Moentamaria; Ariani; Wianthi Septia Witasari; Christyfani Shinduwati (Jurnal Pengabdian kepada Masyarakat, 2022)
Pohjentrek is one of the sub-districts of 7 sub-districts in Purworejo District, Pasuruan City. PKK is the main pengengak between the state and village women so it is very important in the government. In order to increase the PKK group building effort, it is necessary to provide skills training to be more independent so that they have a more decent job and livelihood. One of the skills that can be trained is making solid bath soap. Solid bath soap is needed in everyday life by everyone. Making this solid bath soap is relatively easy and can be made with ingredients that are not difficult to find. The purpose of this PkM is to provide technical guidance for making solid bath soap to the PKK RT.01 / RW.01 Pohjentrek Pasuruan group. Implementing training activities for making solid soap online to the PKK RT.01 / RW.01 Pohjentrek group on October 2, 2020. The publication of these activities was carried out through the Chemical Engineering Department website on October 27, 2020 and through the youtube channel of the Department of Chemical Engineering, State Polytechnic of Malang.